The Influence of Electronic Word of Mouth on Purchase Intention Mediated by Brand Image (A Study on Avoskin Product Consumers in Shopee E-Commerce of Denpasar City) - Dimas Rizal Saputra; I Made Jatra (International Journal of Management Research and Economics, 2024)
The aim of this research is to determine Electronic Word of Mouth on Brand Image-mediated purchase intentions among Shopee E-commerce consumers in Denpasar City. The methodology in this research is associative research. The sampling technique used in this research was non-probability sampling, purposive sampling with a sample size of 100 respondents. The data analysis technique used is descriptive analysis and Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results of this research suggest (1) Electronic Word of Mouth has a positive and significant effect on purchase intention, (2) Electronic Word of Mouth has a positive and significant effect on Brand Image, (3) Brand Image has a positive and significant effect on purchase intention (4) Electronic Word of Mouth has a positive and significant influence on purchase intention which is mediated by Brand Image.